Adaptive recommendation to dynamically changing profiles for delivery of ubiquitous services. (2016) - Amato, Alba; Martino, Beniamino Di; Scialdone, Marco; Venticinque, Salvatore
Many application contexts can benefit from a tight coupling between pervasive objects and services for the delivery of context-aware ubiquitous services. Context awareness is relevant for providing added value services especially in archaeological sites. Visitors could be interested only in specific categories and could be bored by the remaining information. Also, relevant recommendations can change the user's interests giving him a deeper information so stimulating his curiosity. For this reason, the user's profile may change over time, especially if the activity is taking place in a limited time. In this paper, we focus on the utilisation of semantic techniques to support context awareness of ubiquitous services. We propose a metric to compute the similarity between annotations of multimedia contents and the user profile and an optimisation technique to filter the relevant recommendations. The user profile is represented by ontology concepts, which are automatically updated by observing the user behaviour.